PERBANDINGAN PENGARUH PEMBERIAN JUS BUAH NAGA MERAH(HYLOCEREUS POLYRHIZUS) DENGAN OBAT SIMVASTATIN TERHADAP PENURUNAN KADAR KOLESTEROL DARAH MENCIT (MUS MUSCULUS) DENGAN KONDISI HIPERKOLESTEROLEMIA - Nabasa, Gayus Erino; Jawi, I Made; Satriyasa, Bagus Komang (E-Jurnal Medika Udayana, 2023)
This study aims to determine the effect of giving red dragon fruit juice with graded doses on reducing total cholesterol levels of mice with hypercholesterolemic conditions. This research was conducted to prove the anti-cholesterol effect of red dragon fruit juice with a dose variation of 0.39 gr / 30grBB 0.65 gr / 30grBB and 0.91 gr / 30grBB in Swiss male mice with high cholesterol conditions. The subjects of this study were 30 Swiss mice which were divided randomly into 5 groups. This study was an experimental study with a pre-test and post-test control group design. Group 1 as a negative control (high cholesterol diet), group 2 as a positive control. (high cholesterol diet and simvastatin drug), and group 3 (high cholesterol diet and red dragon fruit juice 0.39 gr / 30grBB), group 4 (high cholesterol diet and red dragon fruit juice 0.65 gr / 30grBB), group 5 (high cholesterol diet and red dragon fruit juice 0.91 gr / 30grBB).The parameters measured were the total cholesterol level of mice using the easy touch GCU tool. The data of the results of the study were analyzed by one way ANOVA test with a significance level of ? = 5% with multiple comparisons (Post Hoc Test) LSD type. The results of the study with various doses showed a decrease in total cholesterol levels by 10%; 11%; 15%. The dose variation in this study gave the best results to reduce total cholesterol levels, namely at a dose of 0.91 gr / 30grBB.Based on the result of the study, shows that he administration of red dragon fruit juice showed a significant difference in total cholesterol blood levels of mice. Keywords : Red dragon fruit juice , Cholesterol , Antosianin , Total cholesterol